О ФОРМИРОВАНИИ ЮРИДИЧЕСКИМ ИНСТИТУТОМ СЕВЕРО-КАВКАЗСКОГО ФЕДЕРАЛЬНОГО УНИВЕРСИТЕТА ФИНАНСОВОЙ КУЛЬТУРЫ НАСЕЛЕНИЯ: ВОПРОСЫ ТЕОРИИ И ПРАКТИЧЕСКОЙ РЕАЛИЗАЦИИ - Dmitrii Smirnov; Maxim Trofimov (Гуманитарные и юридические исследования)
Legal culture is an important component of the common culture of a man and a citizen. The level of its wealth and development depends on the overall cultural and legal level of society. Consequently, the underdevelopment of the legal culture leads to the increase in the level and number of offenses committed, low legal literacy manifested in ignorance of the law and the lack of basic skills for citizens to protect their rights. Part of the overall legal culture and literacy of a person is financial culture and literacy. In recent years, the Russian Federation, similar to western countries decades ago, pays great attention to the formation of the financial literacy of the population through the implementation of various national programs. An important role in the formation of financial culture and financial literacy is played by the Institute of Law of the North-Caucasus Federal University. The article reveals the concept and structure of the financial culture of a man and society in the Russian Federation, and also reveals and describes the problems of financial sense of justice of participants in financial legal relations. The authors draw attention to the problems of forming the financial literacy of the population of Russia by the example of the Stavropol Krai and offer a number of measures to strengthen the financial culture.